Kantian Ethics, Feminism, and Worries about Emotional Detachment - Baron, Marcia (Studia Kantiana, 2023)
This essay is a much-revised version of my “Kantian Ethics and Claims of Detachment” (Baron, 1997). I am grateful to the editors at Penn State University Press for permitting me to use the material in that paper in this one. My essay addresses three criticisms of Kant’s ethics, all involving the notion of detachment: that it requires us to be detached from other persons (at the very least, to hold them at arm’s length); that it requires us to have a sort of detachment from our own projects; and that it requires detachment from feeling. I frame these worries in terms of a broader question of whether Kant’s ethics is deeply or only very superficially at odds with feminism, doing so in light of claims by some feminists that it is indeed deeply at odds with it.